2023
DOI: 10.3390/ijms24043858
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of Respiratory Burst Oxidase Homolog (RBOH) Genes in Plants and Characterization of ZmRBOHs

Abstract: The respiratory burst oxidase homolog (RBOH), as the key producer of reactive oxygen species (ROS), plays an essential role in plant development. In this study, a bioinformatic analysis was performed on 22 plant species, and 181 RBOH homologues were identified. A typical RBOH family was identified only in terrestrial plants, and the number of RBOHs increased from non-angiosperms to angiosperms. Whole genome duplication (WGD)/segmental duplication played a key role in RBOH gene family expansion. Amino acid numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 77 publications
5
15
0
Order By: Relevance
“…The RBOH genes found scattered on few chromosomes in various plants (Gui et al 2022;Zhang et al 2023;Sharma et al 2024). Similarly, the VraRBOH genes showed their presence on ve chromosomes, whereas six chromosomes have not shown the presence of any RBOH gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RBOH genes found scattered on few chromosomes in various plants (Gui et al 2022;Zhang et al 2023;Sharma et al 2024). Similarly, the VraRBOH genes showed their presence on ve chromosomes, whereas six chromosomes have not shown the presence of any RBOH gene.…”
Section: Discussionmentioning
confidence: 99%
“…In biological systems, the gene duplication occurs by three mechanisms namely tandem duplication, segmental duplication and whole-genome duplication (WGD) [Qiao et al 2018]. The whole genome duplication of RBOH genes have previously demonstrated as driving force for gene duplication events related to RBOH genes in crop plants Zhang et al 2021;Wu et al 2023;Zhang et al 2023). Notably, one tandemly duplicated gene pair (VraRBOH4 and VraRBOH5) and 3 segmental gene duplication events were predicted in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of ROS in promoting pollen tube growth, which has been discovered in other plant species (Kaya et al, 2014; Lassig et al, 2014; Kim et al, 2021), has not been reported in maize. The maize genome harbors 15 ZmRBOH s (Zhang et al, 2023); further research is needed to elucidate the roles of specific ZmRBOH s in pollen tube growth.…”
Section: Roles Of Ros In Maize Developmentmentioning
confidence: 99%
“…Superoxide is converted to H 2 O 2 by superoxide dismutase (SOD) and enters into cells via aquaporin proteins (see Figure 2 in Martin et al, 2022). In Arabidopsis , the RBOH family contains 10 genes and the functionality of these enzymes has been conserved across diverse species and tissue types (Chapman et al, 2019; Zhang et al, 2023). ROS are also products of metabolism in organelles such as mitochondria and chloroplasts that generate ROS through electron transport chains (Foyer & Hanke, 2022; Møller, 2001; Navrot et al, 2007).…”
Section: Introductionmentioning
confidence: 99%